Impact of electrical stress on total ionizing dose effects on graphene nano-disc non-volatile memory devices. (November 2020) - Xi, K.; Bi, J.S.; Xu, Y.N.; Li, Y.D.; Zhang, Z.G.; Liu, M.
Abstract: The impact of electrical stress on the effects of total ionizing dose (TID) on graphene nano-disc non-volatile memory (GND-NVM) devices is investigated by X-ray irradiation with doses ranging from 50 to 1000 krad. The electrical characteristics of the devices are measured at each dose step and are compared to those before X-ray exposure. Applying non-zero gate stress during irradiation significantly accelerates the degradation process, and the device fails with an unusable memory window at a TID dose of 500 krad. The electric field in the surrounding oxides plays a key role in the observed degradation. Highlights: The impact of electrical stress on the effects of total ionizing dose (TID) on graphene nano-disc non-volatile memory (GND-NVM) devices is investigated. Applying non-zero gate stress during irradiation significantly accelerates the degradation process due to the electric field in the surrounding oxides.